Economic Abuse and Care-seeking Practices for HIV and Financial Support Services in Women Employed by Sex Work: A Cross-Sectional Baseline Assessment of a Clinical Trial Cohort in Uganda. Issue 1 (January 2023) - Jennings Mayo-Wilson, Larissa; Yen, Bing-Jie; Nabunya, Proscovia; Bahar, Ozge Sensoy; Wright, Brittanni N.; Kiyingi, Joshua; Filippone, Prema L.; Mwebembezi, Abel; Kagaayi, Joseph; Tozan, Yesim; Nabayinda, Josephine; Witte, Susan S.; et al.
Economic hardship is a driver of entry into sex work, which is associated with high HIV risk. Yet, little is known about economic abuse in women employed by sex work (WESW) and its relationship to uptake of HIV prevention and financial support services. This study used cross-sectional baseline data from a multisite, longitudinal clinical trial that tests the efficacy of adding economic empowerment to traditional HIV risk reduction education on HIV incidence in 542 WESW. Mixed effects logistic and linear regressions were used to examine associations in reported economic abuse by demographic characteristics, sexual behaviors, HIV care-seeking, and financial care-seeking. Mean age was 31.4 years. Most WESW were unmarried (74%) and had less than primary school education (64%). 48% had savings, and 72% had debt. 93% reported at least one economic abuse incident. Common incidents included being forced to ask for money (80%), having financial information kept from them (61%), and being forced to disclose how money was spent (56%). WESW also reported partners/relatives spending money needed for bills (45%), not paying bills (38%), threatening them to quit their job(s) (38%), and using physical violence when earning income (24%). Married/partnered WESW (OR = 2.68, 95% CI:1.60–4.48), those with debt (OR = 1.70, 95% CI:1.04–2.77), and those with sex-work bosses (OR = 1.90, 95% CI:1.07–3.38) had higher economic abuse. Condomless sex ( β = +4.43, p < .05) was higher among WESW experiencing economic abuse, who also had lower odds of initiating PrEP (OR = .39, 95% CI:.17–.89). WESW experiencing economic abuse were also more likely to ask for cash among relatives (OR = 2.36, 95% CI:1.13–4.94) or banks (OR = 2.12, 95% CI:1.11–4.03). The high prevalence of HIV and economic abuse in WESW underscores the importance of integrating financial empowerment in HIV risk reduction interventions for WESW, including education about economic abuse and strategies to address it. Programs focusing on violence against women should also consider economic barriers to accessing HIV prevention services.